Investigation of the effect of pilot hole diameter, pilot hole depth and thickness on screw direct withdrawal resistance in OSB - Birinci, Emre; Kaymakcı, Alperen (Cankiri Karatekin Universitesi, 2025)
Background and aims OSBs are an engineered wood-based composite material and is widely used especially in the construction and furniture sectors. Screw connections are one of the critical elements that determine the mechanical strength of OSB. The aim of this study is to investigate the effects of pilot hole diameter, pilot hole depth and board thickness on the screw direct withdrawal resistance in OSB. In the study, screw direct withdrawal resistance was tested by using 11mm and 18mm thick OSBs, taking into account different pilot hole diameters (60% and 85%), pilot hole depths (50% and 80%) and screwing directions (edge and face). Methods Uncoated 11mm and 18mm thick OSBs were used in the experiments. Zinc-plated sheet steel screws 3.5×30mm were used. Results The results showed that pilot hole diameter, depth, and screwing direction significantly affected screw withdrawal resistance. A 60% pilot hole diameter and 50% depth provided higher resistance than 85% and 80%, respectively. Face screwing yielded greater strength than edge screwing. While OSB thickness had no significant effect, 18 mm boards showed slightly higher resistance on average. Conclusions The factors should be selected correctly in order to use OSBs more safely and efficiently in engineering and construction applications. In particular, it is recommended to prefer face screwing and to use a pilot hole diameter of 60% and a depth of 50% in proportion to the screw diameter. These findings will contribute to the creation of more reliable and durable connections in the areas where OSBs are used.